Dynamic load balancing in parallel processing on non-homogeneous clusters - Armando Eduardo De Giusti; Marcelo Naiouf; Laura Cristina De Giusti; Franco Chichizola (Journal of Computer Science and Technology, 2005)
This paper analyzes the dynamic and static balancing of non-homogenous cluster architectures, simultaneously analyzing the theoretical parallel Speedup as well as the Speedup experimentally obtained. Three interconnected clusters have been used in which the machines within each cluster have homogeneous processors although different among clusters. Thus, the set can be seen as a 25-processor heterogeneous cluster or as a multi-cluster scheme with subsets of homogeneous processors. A classical application (Parallel N-Queens) with a parallel solution algorithm, where processing predominates upon communication, has been chosen so as to go deep in the load balancing aspects (dynamic or static) without distortion of results caused by communication overhead. At the same time, three forms of load distribution in the processors (Direct Static, Predictive Static and Dynamic by Demand) have been studied, analyzing in each case parallel Speedup and load unbalancing regarding problem size and the processors used.